ОСОБЛИВОСТІ ВИКОРИСТАННЯ ERP- І CRM- СИСТЕМ ДЛЯ АВТОМАТИЗАЦІЇ УПРАВЛІННЯ ПІДПРИЄМСТВОМ - Kovpaka, Anastasiya; Saukh, Iryna; Pavlova, Svitlana (Zhytomyr Ivan Franko State University, 2022)
This publication is devoted to the problem of informatization and automation of management at the enterprise. The study found that the use of innovative systems is becoming increasingly popular in the Ukrainian market. Automation plays a crucial role in ensuring the growth of efficiency indicators of economic activity, but among domestic enterprises, there is a problem in choosing the use of a particular information system. This article describes the main advantages and disadvantages of ERP and CRM systems. Approaches to definitions are defined, and the concepts of ERP and CRM as methodologies of effective resource planning and system of automation of interaction with clients are revealed. A comparative analysis of ERP and CRM systems is carried out. The main functions of CRM systems are studied, among which: are the formation of a single information client base; working time management; optimization of communications within the company; sales planning. The place of the customer in the customer relationship management system is determined. The main modules of the ERP system are analyzed, namely: finance, personnel, sales, procurement, production, logistics, service, research and development, and assets. A detailed description of the functional solution when using the resource management system is given. The main tools of ERP and CRM systems are identified. As a result of the analysis of the modern market of information systems the main suppliers of software products and their weight in the given market segment are defined. A number of software products of ERP and CRM systems popular in Ukraine have been studied. The level of implementation of CRM systems by industry structure is determined. It is established that the maximum result from the implementation of CRM systems is possible only when they are implemented together with the integrated internal ERP system.